OPTIMASI DOSIS PUPUK KALSIUM DAN BORON UNTUK MENGENDALIKAN CEMARAN GETAH KUNING PADA BUAH MANGGIS - Purnama, Titin (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2016)
Yellow latex is commonly called gamboge and is a latex produced in all parts of the mangosteen. Yellow sap becomes a problem when it gets out of the ruptured channel, and contaminates the aryl and pericarp. Ruptured channel of yellow latex is presumably because the walls of the epithelial cells of the yellow latex channels is Calcium deficiency. In addition, Boron has also the same function in maintaining the integrity of the cell wall. This research was aimed to know the roles of calcium and boron in controlling contamination yellow latex on the mangosteen fruit, and to obtain the best combination between calcium and boron in preventing the yellow latex contamination on mangosteen. The study was conducted in Purwakarta, West Java from November 2012 to June 2013. The study was arranged a randomized factorial with three replications. The treatment consists of two factors: dosages of Ca (0.0; 2.5; 5.0 and 7.5 kg / tree) and of B (0.00; 0.77; 1.55 and 2.32 g /tree). There was no interaction effect observed between calcium and boron fertilizer on fruit physical and chemical variables but there were significant interactions in quadratic levels of yellow latex contaminant in the mangosteen fruit. The percentage of fruit with minimum aryl contamination was 1.05 % at the optimum combination dose of 5.0 kg Ca/tree and 1.55 g B2O3/tree.